A produção científica da Ciência da Informação no Brasil: análise do período 2010 a 2020 nas bases de dados Scopus e Web of Science - Sônia Mônica da Silva (2021)
The research focus on analyzing the scientific production of Information Science in Brazil, from 2010 to 2020, published in journals indexed in the Scopus and Web of Science databases. It is a descriptive research with quantitative and qualitative approaches. The quantitative approach will use bibliometric and scientometric techniques to support the measuring of researchers’ productivity. It was decided to identify the keywords and the relevance in the studied period. For that, Hawkins Information Science Taxonomy was used. The data analysis procedures include some categories: title of the article, author, author’s institutional origin, collaboration, year of publication. To identify the main themes, considered that the quest for research and the return are very different in the two bases, it was decided to describe and analyze the results of each database separately. It is noticed that Scopus has more coverage than the Web of Science. When surveying scientific production in the period from 2010 to 2020 in the Scopus and Web of Science databases, 3,000 articles and reviews were found. The survey of scientific production in the period from 2010 to 2020 in the Scopus database resulted in 2,206 articles and literature reviews, of which 2023 (92%) of the indexed documents are in the form of articles and 183 (8%) are reviews of literature. Publications increased from 99 publications in 2010 to 348 in 2019 and recorded a decrease in 2020. The twelve taxonomy themes were analyzed with more evidence in the articles. There are three important themes: Information Science, Library and Librarianship. The Scopus database found 6,886 authors who produced 2,206 articles and reviews in the period from 2010 to 2020. The authors who produced ten or more articles in the period were very prominent in the research. It was found that 30 authors (20%) are responsible for 36.72% of productivity, with an average of 12 articles published in the period. When analyzing the production of articles with co-authorship in the area of Information Science in the period 2010-2020, an expressive institutional collaboration is noted in the total academic production. Institutional collaboration corresponds to 34% of academic production and international collaboration with 22% of articles. The production of articles in the Scopus database was disseminated in 70 journals. The Perspectives in Information Science and Information Science journals were the most productive. These two journals published 752 articles, or 34% of the total production. In the Web of Science database, the scientific production from 2010 to 2020 produced 796 articles and reviews. Production went from 43 to 125 articles (65.6%) from 2010 to 2017 and decreased from 2018 to 2020. For the analysis of the main themes, the analysis of the keywords was chosen. The most prominent themes are Information Science (20.52%), Information Competence (10.26%) and Information (6.99%). Acoording to the categorization in the Taxonomy table by Hawkins et al. (2003), the theme Libraries and library services were the most researched. The production of each author in the period studied in the Base Web of Science shows the productivity of 1,093 authors for 796 articles. 774 authors (70.81%) published only one article in the period. Scientific collaboration between authors shows that 113 (14.20%) published articles were published by individual authors. The most expressive way of collaboration is between two authors with 383 articles (48.12%). The 796 articles indexed in the Base Web of Science are distributed in 15 journals. The three most productive were Information Society Studies with 254 articles (31.47%), Perspective in Information Science with 177 articles (21.93%) and Transformation with 116 articles (14.37%). To characterize the most productive programs, the following references were adopted: year of beginning of the programs, number of teachers working on the programs, areas of concentration of the programs, the stricto sensu postgraduate modalities of each program, the evaluation by CAPES of the master’s degree and Phd and regional location. There is a concentration of programs in the Southeast region. The results point to a significant production during 2010-2020. The Information Science area still needs a broader maturation process to consolidate studies.